(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
TiO2 is one of the most often used pigment ingredients in paints due to its many benefits. TiO2 can be used as a filler material in concrete to fill in cracks, voids, fissures, bleeding channels, and other gaps, hence increasing the concrete’s strength. The goal of the current work is to examine how well M40 grade high strength concrete performs when nanomaterials are used. This has been done by partially substituting nano titanium dioxide (tio2) for cement (varying from 0.5% to 2%). By performing the slump cone test and the compaction factor test, it was possible to compare the workability of M40 grade concrete with and without the addition of nano tio2. Finally, compression, split tensile, and flexural tests have been used to assess the strength properties of both types of concrete.